Integrating Photovoltaic Systems in Power System: Power Quality Impacts and Optimal Planning Challenges - Aida Fazliana Abdul Kadir; Tamer Khatib; Wilfried Elmenreich (International Journal of Photoenergy)
This paper is an overview of some of the main issues in photovoltaic based distributed generation (PVDG). A discussion of the harmonic distortion produced by PVDG units is presented. The maximum permissible penetration level of PVDG in distribution system is also considered. The general procedures of optimal planning for PVDG placement and sizing are also explained in this paper. The result of this review shows that there are different challenges for integrating PVDG in the power systems. One of these challenges is integrated system reliability whereas the amount of power produced by renewable energy source is consistent. Thus, the high penetration of PVDG into grid can decrease the reliability of the power system network. On the other hand, power quality is considered one of the challenges of PVDG whereas the high penetration of PVDGs can lead to more harmonic propagation into the power system network. In addition to that, voltage fluctuation of the integrated PVDG and reverse power flow are two important challenges to this technology. Finally, protection of power system with integrated PVDG is one of the most critical challenges to this technology as the current protection schemes are designed for unidirectional not bidirectional power flow pattern.